UTILIZATION OF SOCIAL MEDIA AND ENTREPRENEUR KNOWLEDGE ON ENTREPRENEUR INTEREST STUDENT OF STIE PEMUDA SURABAYA - Anisa, Nur Aini; Rachma, Evi Aulia; Arifin, Syamsul (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
This study aims to analyze the influence of the use of social media and entrepreneurial knowledge on the entrepreneurial interest of STIE Pemuda students both partially and simultaneously. This research is a descriptive quantitative research. The sample used was 100 students who had taken entrepreneurship courses. The data analysis method uses multiple linear regression analysis techniques. The results showed that partially the use of social media and entrepreneurial knowledge had a positive and significant effect on the entrepreneurial interest of STIE Pemuda Surabaya students. Simultaneously that the use of social media and entrepreneurial knowledge has a positive and significant effect on the entrepreneurial interest of STIE Pemuda Surabaya students